Exploring the causes of semen quality changes post-bariatric surgery: a focus on endocrine-disrupting chemicals. Issue 5 (31st March 2022) - Magalhaes, Danielly P; Mahalingaiah, Shruthi; Perry, Melissa J
Abstract: Rapid weight loss promoted by bariatric surgery (BS) can release accumulated lipophilic endocrine-disrupting chemicals (EDCs), making these chemicals systemically available. Men typically have a higher EDC body burden and lose more weight post-BS than women, which may put male BS patients at high risk for testicular toxicity. In this review, we analyze the impacts of BS on semen parameters with a particular focus on the potential effects of EDCs. After BS, serum EDC concentrations progressively increase; and there is evidence that semen parameters deteriorate after BS. Although elevated serum EDC concentrations are associated with inferior sperm parameters, links between semen parameters and EDCs post-BS have not been studied. Understanding these potential associations requires adequately powered studies, particularly within prospective longitudinal cohorts with long-term follow-up for sperm parameters, nutritional status, sex-hormones levels and serum EDC concentrations. Studying BS patients prospectively provides the important opportunity to evaluate dose–response effects of EDC serum concentrations on sperm quality and function. Research is also needed to identify critical chemical exposure periods post-BS to inform reproductive decisions, including consideration of sperm preservation before surgery.